Interactions of microorganisms and synthetic polymers in cultural heritage conservation. (September 2021) - Cappitelli, Francesca; Villa, Federica; Sanmartín, Patricia
Abstract: Since the 1960s, synthetic polymers (at the time assumed to be resistant to microbial colonization) have been employed to mitigate the ongoing deterioration of cultural heritage. Since then, the use of synthetic materials in heritage conservation attracted much interest. This paper reviews the last two decades of advances in the relationship microorganisms - synthetic polymers in the cultural heritage conservation field. Three topics are considered: (1) biodeterioration of traditional synthetic polymers, (2) biosusceptibility of novel composites based on synthetic polymers, and (3) biocleaning to remove undesired synthetic polymers. It is know that, if the undesired polymer chemical structures are not fully known, they are particularly difficult to remove. Therefore, the future employment of synthetic polymers definitely requires a more critical holistic conservation assessment. Highlights: Biodeterioration of synthetic polymers in conservation is a concern. Synthetic polymer-based composites are susceptible to microbial attack. Selected microorganisms are used to remove undesired synthetic polymers. Current research gaps and priorities are defined.